Discharge of Debts of Insolvent Entrepreneurs Under the Restructuring and Insolvency Directive - Jokubauskas, Remigijus (Utrecht Journal of International and European Law, 2023)
The article focuses on the discharge procedure for entrepreneurs as prescribed in the Directive on restructuring and insolvency. It analyses the elements of the discharge procedure for entrepreneurs that are harmonised with the Directive and whether it ensures a proper balance between the interests of the debtor and creditors. The author assesses how the concept of an ‘entrepreneur’ should be perceived under the scope of the Directive, the requirements of commencement of discharge of debt procedure and whether it indeed provides a fresh start for entrepreneurs after the end of this procedure. Where relevant, the article focuses on the comparison between the discharge procedure in the Directive and the rules of personal bankruptcy established in the US Bankruptcy Code (Chapters 7 and 13) which served as an inspiration to the Directive. Comparison of the relevant rules on the discharge procedures established in the Directive and the US Bankruptcy Code allows us to better understand the aims and goals of certain provisions of the discharge procedure in the European Union insolvency law and provide a conclusion on whether the proposed model of discharge procedure is effective. The author discusses whether the discharge procedure in the Directive managed to establish a fair balance between the interests of the debtor and creditors and whether it will improve entrepreneurship conditions in the European Union.